Improving Secondary School Students' Achievement and Retention in Biology Through Video-Based Multimedia Instruction - Amosa Isiaka Gambari; Akawo Angwal Yaki; Eli S. Gana; Queen Eguono Ughovwa (Park University, 2014)
The study examined the effects of video-based multimedia instruction on secondary school students' achievement and retention in biology. In Nigeria, 120 students (60 boys and 60 girls) were randomly selected from four secondary schools assigned either into one of three experimental groups: Animation + Narration; Animation + On-screen Text; Animation + Narration + On-screen Text or a control group. The pretest, posttest experimental, and control group design was adopted. A 50-item multiple-choice objective test termed Biology Achievement Test (BAT) was used for collecting data. The validated BAT was tested for reliability using Kuder Richardson (KR20), which yielded 0.89. T-test, analysis of covariance (ANCOVA), and Scheffe's post-hoc analysis were used in determining the significant differences among the four groups. The results showed that there was no statistically significant difference among the experimental groups. Generally, students under multimedia instruction performed better than their colleagues in the conventional teaching method. However, students in conventional teaching method had better retention than other groups.